2D Nanomaterial-Based Hybrid Structured (Au-WSe2-PtSe2-BP) Surface Plasmon Resonance (SPR) Sensor With Improved Performance - Md. Mahabubur Rahman; Lway Faisal Abdulrazak; Mominul Ahsan; Md. Abdul Based; Md. Masud Rana; Md. Shamim Anower; Khaleda Akter Rikta; Julfikar Haider; Saravanakumar Gurusamy (IEEE Access, 2022)
As a promising optical method used in a variety of applications surface plasmon resonance (SPR) sensors are employed over a wide range of boundaries. This research proposes a highly sensitive SPR based sensor with a novel hybrid structure using transition metal dichalcogenides (e.g. WSe2, PtSe2) along with black phosphorene (BP) through comprehensive numerical study. To analyze and evaluate the performances of the proposed sensor, the widely used transfer matrix method (TMM) was used. The performances of the sensor were measured in terms of reflectivity, sensitivity, detection accuracy (DA), and figure of merit (FOM). The sensor structure was optimized by changing different structural parameters of the hybrid architecture to obtain better performances. The results revealed that insertion of PtSe2 with WSe2 and BP over a gold layer of the conventional structure improved the performance of the sensor and the maximum sensitivity of the sensor was measured as 200 deg/RIU with a FOM of 17.70 RIU−1. As well, the light penetration through the optimized sensor is investigated using the finite element method (FEM) based software. With this kind of high sensing capabilities, it may be convinced that the proposed sensor can be applied in different fields of biosensing to detect liquid biological and biochemical samples or analytes.